The Therapeutic Potential of Humic Acid in Streptozotocin-Induced Hyperglycemic White Rats (Rattus norvegicus L.) - Sirait, Evi Marina; Rousdy, Diah Wulandari; Yanti, Ari Hepi (Jurnal Riset Biologi dan Aplikasinya, 2025)
Humic acid, an organic compound from peat soil, rich in antioxidants such as quinone and phenol, shows potential as an antidiabetic agent. This study aims to identify the optimal dose of humic acid extract for increasing body weight, lowering blood glucose levels, reducing malondialdehyde (MDA) levels, and improving the microanatomical structure of the pancreas in streptozotocin-induced diabetic rats. The humic acid was extracted from peat soil at Tanjungpura University. The study utilized 25 male Wistar rats (Rattus norvegicus), aged 8-12 weeks, organized in a group randomized design (GRD). Interventions included a single dose of streptozotocin (40 mg/kg b.w.) and varying doses of humic acid extract administered over 14 days post-induction. Results indicated that a dose of 375 mg/kg b.w. humic acid extract resulted in an increased final body weight by 11.86%, a reduction in fasting blood glucose levels by 79.23%, an AUC0-120 value of 19.311, and a final MDA level of 1.09 ±0.27 nmol/ml. These findings indicate the potential of humic acid as a therapeutic agent for diabetes.